URBANIZATION, MIGRATION, AND HUMAN SECURITY: IMPLICATIONS FOR SUSTAINABLE DEVELOPMENT IN AFRICA - Damian Kehinde Adesegha; Adeshina Iyanuoluwa Omotayo (International Studies Journal)
Urbanization refers to the gradual increase in the proportion of a population living in urban areas, and the corresponding decline in rural areas. Migration is also global phenomenon that involves a complex and multifaceted process that deals with the movement of individuals or groups from one geographical location to another for various reasons. Today, urbanization continues to be a major trend worldwide, with more than half of the world's population now living in urban areas. At its core, the concept of human security emphasizes the protection and empowerment of people, rather than just states or territories. This study examines the complex relationship between urbanization, migration, and human security in Africa and their implications for sustainable development. The continent's rapid urbanization and internal migration have created new challenges for policymakers, particularly in the areas of human security and sustainable development. While urbanization can be a driver of economic growth and human development, it also poses significant challenges to human security. Urbanization and migration often lead to overcrowding, inadequate housing, and limited access to basic services such as water and healthcare. These conditions increase the vulnerability of urban populations to a range of security threats, including crime, disease outbreaks, and environmental disasters.